PENDEKATAN EKSISTENSIAL HUMANISTIK DALAM KONSELING ISLAM - LUTHFA AF IDATI, ATA (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2024)
This literature research presents a comprehensive overview of the incorporation of existential-humanistic counseling approaches in the context of Islamic counseling. Against the backdrop of the urgency of providing counseling services to the predominantly Muslim community and then drawing parallels between existential-humanistic concepts and Islamic principles, this research provides a richer view for counseling practitioners working with Muslim counselees. The main focus of this research is to identify and evaluate the ways in which existential humanistic counseling principles can be applied and integrated with the values and principles of Islamic teachings in the counseling process. Through an analysis of current literature, this study reveals that an existential humanistic counseling approach integrated with Islamic values can provide a strong foundation for understanding and addressing individual psychological problems. The deep understanding of existence, freedom, and the search for meaning in this approach is in line with Islamic values such as faith, tawakal, and a meaningful purpose in life. The implication of this literature review is to strengthen the integration between the humanistic existential counseling approach and Islamic counseling principles, providing a solid foundation for culturally and religiously sensitive counseling practice. It is hoped that this research can contribute to a better understanding of how a holistic counseling approach can be adapted to empower Muslim individuals in achieving psychological and spiritual well-being